Therapeutic potential of placenta-derived stem cells cultivated on noggin-loaded nanochitosan/polypyrrole-alginate conductive scaffold to restore spinal cord injury - Asma Manzari-Tavakoli; Amirhesam Babajani; Nasim Vousooghi; Ali Moghimi; Roghayeh Tarasi; Fahimeh Safaeinejad; Samira Norouzi; Soheyl Bahrami; Hassan Niknejad (Stem Cell Research & Therapy)
Abstract Objective Spinal cord injury (SCI) is a severe and permanent nerve damage condition that poses significant burdens on individuals and society. Various therapeutic approaches have been explored to mitigate the consequences of SCI. Tissue engineering and regenerative medicine have emerged as a promising avenue for addressing this issue. This study aims to investigate the potential of a nanochitosan/polypyrrole-alginate conductive scaffold, loaded with the Noggin growth factor, an inhibitor of BMP-4 signaling, and human amniotic epithelial cells (hAECs), in promoting the regeneration of SCI in animal models. Methods The attachment and distribution of isolated hAECs on a fabricated nanochitosan/polypyrrole-alginate conductive scaffold were assessed using SEM. Additionally, the neural differentiation of hAECs on the scaffold was investigated by analyzing the expression of specific neuronal (Calca, Fox3), oligodendrocyte (MBP), and astrocyte (GFAP) genes in vitro. To evaluate the combined effect of the scaffold and Noggin growth factor in animal models, a Noggin-loaded scaffold was designed using bioinformatics, and the loading and release capacity of Noggin were measured. For in vivo studies, rats underwent laminectomy and were transplanted with the scaffold, either alone or with Noggin and DII labeled- hAECs, at the T10-T11 level. Motor functions of the animal were evaluated using BBB scoring weekly in an open field for four weeks. Furthermore, the expression of neural genes and immunohistochemical tests were evaluated after four weeks. Results hAECs exhibited uniform distribution and attachment to the scaffold. In vitro differentiation analyses showed increased expression of Calca, Fox3, MBP, and GFAP genes. Docking results indicated that Noggin could interact with chitosan nanoparticles through hydrogen bonds. The chitosan nanoparticles effectively loaded 22.6% of exposed Noggin, and the scaffold released 28.5% of the total incorporated Noggin. In vivo studies demonstrated that transplanting nanochitosan/polypyrrole-alginate conductive scaffolds with DII labeled-hAECs, with or without Noggin, improved motor functions in animal models. The assessment of gene expression patterns in transplanted hAECs revealed that neuronal (Calca, Fox3) and oligodendrocyte (MBP) genes in the injured spinal cord of the animal models were upregulated. Histopathological analysis showed a reduction in inflammation and glial scar formation, while neural fiber regeneration increased in the treated animals. Also, DII labeled-hAECs in the lesion site were alive after a period of four weeks. Conclusion Based on these findings, it can be inferred that the integrative therapeutic effects of human amniotic epithelial cells, nanochitosan/polypyrrole-Alginate conductive scaffold, and Noggin (as BMP-4 signaling inhibitor) represents a promising and innovative approach in the field of translational medicine.